Land combat from World War I to the present day - Dougherty, Martin J. (Amber Books Ltd, 2016)
"Since 1914 the art and increasingly science of warfare has become ever deadlier. Tanks have become more mobile and more protected, artillery has come to dominate battlefields and even ordinary infantrymen are now equipped with body armor and lightweight fully automatic weapons, usually fitted with magnifying scopes.Containing full-color artworks and action photographs, Land Combat is a comprehensive guide to how wars have been fought since the outbreak of World War I. All of the most famous wars and campaigns are featured, from the Western Front to the Blitzkrieg, the Arab-Israeli wars and Vietnam, up to the Gulf and the present day. Land Combat is an authoritative guide to the development of the fighting techniques used on the battlefield from 1914 to today."